Associations of maternal cyclin-dependent kinase 5 regulatory subunit-associated protein 1-like 1(CDKAL1) gene variants with adverse pregnancy outcome in Chinese women - Shuoying Yue; Meng Su; Zihao Zhang; Jing Li; Junhong Leng; Weiqin Li; Jin Liu; Tao Zhang; Yijuan Qiao; Zhijie Yu; Gang Hu; Jun Ma; et al. (BMC Pregnancy and Childbirth)
Abstract Objective To test associations of cyclin-dependent kinase 5 regulatory subunit-associated protein 1-like 1 (CDKAL1) gene variants with the risk of adverse pregnancy outcome in Chinese women and whether the association was mediated by occurrence of gestational diabetes mellitus. Methods We organized a 1:1 age-matched study nested within a prospective cohort of pregnant women (207 pairs) established in urban Tianjin. Adverse pregnancy outcome was defined as a composite outcome of preterm birth, low birth weight or macrosomia. Logistic regression analyses were used to estimate associations of CDKAL1 gene variants with adverse pregnancy outcome and its components. The CDKAL1 genetic marker was defined as encompassing any of the identified susceptibility variants for adverse pregnancy outcome. Results The CDKAL1 genetic marker was associated with the risk of adverse pregnancy outcome (OR: 2.51, 95%CI: 1.47, 4.28), low birth weight (OR: 19.80, 95%CI: 2.15, 182) and macrosomia (OR: 2.40, 95%CI: 1.17, 4.93), but not with preterm birth (P = 0.105) after adjusting for traditional risk factors. Further adjusting for gestational diabetes mellitus, the CDKAL1 genetic marker remained significantly associated with adverse pregnancy outcome, and the OR (95%CI) was 2.52 (1.48, 4.30). Conclusion The maternal CDKAL1 gene variants were associated with increased risk of adverse pregnancy outcome, low birth weight and macrosomia, independent of gestational diabetes mellitus. CDKAL1 gene might be a useful marker for identification of individuals at a particularly high risk of adverse pregnancy outcome in early pregnancy.